Allocating Risks in Public-Private Partnerships Using a Transaction Cost Economic Approach: A Case Study - Xioa-Hua Jin (Australasian Journal of Construction Economics and Building, 2012)
Public-private partnership (PPP) projects are often characterisedby increased complexity and uncertainty due to their idiosyncrasyin the management and delivery processes such as long-termlifecycle, incomplete contracting, and the multitude of stakeholders.An appropriate risk allocation is particularly crucial to achievingproject success. This paper focuses on the risk allocation in PPPprojects and argues that the transaction cost economics (TCE)theory can integrate the economics part, which is currently missing,into the risk management research. A TCE-based approach isproposed as a logical framework for allocating risks between publicand private sectors in PPP projects. A case study of the SouthernCross Station redevelopment project in Australia is presented toillustrate the approach. The allocation of important risks is putunder scrutiny. Lessons learnt are discussed and alternativemanagement approaches drawing on TCE theory are proposed.